2023
DOI: 10.1038/s41467-023-41465-6
|View full text |Cite
|
Sign up to set email alerts
|

1/4 is the new 1/2 when topology is intertwined with Mottness

Peizhi Mai,
Jinchao Zhao,
Benjamin E. Feldman
et al.

Abstract: In non-interacting systems, bands from non-trivial topology emerge strictly at half-filling and exhibit either the quantum anomalous Hall or spin Hall effects. Here we show using determinantal quantum Monte Carlo and an exactly solvable strongly interacting model that these topological states now shift to quarter filling. A topological Mott insulator is the underlying cause. The peak in the spin susceptibility is consistent with a possible ferromagnetic state at T = 0. The onset of such magnetism would convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…This highlights the importance of moiré wavelength as a tuning parameter, which is only accessible in low-twist, lattice-matched systems. Our work motivates further studies to confirm the specific spin/valley symmetry breaking of the odd-integer gaps, as well as transport studies to confirm whether quantum spin Hall insulating states are realized at even integers, including a potential double quantum spin Hall insulator at ν=4 ( 29 ). More generally, this work opens a platform for studying tunable topological bands in the limit of larger moiré wavelengths where interacting phases such as fractional Chern insulators may be more readily stabilized ( 46 , 47 ).…”
Section: Discussion and Outlookmentioning
confidence: 60%
See 3 more Smart Citations
“…This highlights the importance of moiré wavelength as a tuning parameter, which is only accessible in low-twist, lattice-matched systems. Our work motivates further studies to confirm the specific spin/valley symmetry breaking of the odd-integer gaps, as well as transport studies to confirm whether quantum spin Hall insulating states are realized at even integers, including a potential double quantum spin Hall insulator at ν=4 ( 29 ). More generally, this work opens a platform for studying tunable topological bands in the limit of larger moiré wavelengths where interacting phases such as fractional Chern insulators may be more readily stabilized ( 46 , 47 ).…”
Section: Discussion and Outlookmentioning
confidence: 60%
“…Our experiment is most consistent with the pair of lowest-energy moiré bands having identical Chern numbers in a single spin/valley sector (supplementary text S2 and S3). This is beyond any two-band tight binding model (which must have a zero total Chern number), highlighting that the topological structure in tWSe 2 extends beyond the Kane-Mele model ( 26 , 29 , 43 ).…”
Section: Series Of Chern Insulators In Twse2mentioning
confidence: 95%
See 2 more Smart Citations
“…They also highlight the difference between TMD bilayers and graphene multilayers. Already, in the time between this study's preprint and publication, experimentalists have revealed an additional topological phase in the same material [5], and theorists have proposed new models to explain the unusual topological phenomena found in moiré TMDs [6,7]. The new information about valley coherence in twisted MoTe 2 /WSe 2 bilayers will inevitably result in experiments to further elucidate the origin of the zero-field spin pattern and of the QAH effect.…”
mentioning
confidence: 83%